Europe’s Border in Africa: Online Social Reactions to the Ceuta Migration Crisis in Five European Languages - Mariscal-de-Gante, Álvaro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2024)
Albeit migration crises bear crucial societal, political, and diplomatic implications for Spain, this study marks the first computational analysis of real-time online reactions to a Spanish migration crisis since the rise of the far right. Analyzing 195.000 tweets on the Ceuta 2021 crisis, we found that VOX played a major role in shaping the discussion. However, migrant-bashing was not the only, or even the predominant, reaction: social opinions targeted various political, diplomatic, humanitarian, and policy actors. Additionally, this study is the first to assess the discussion in other four European languages, crucial for an EU external border. Results confirm limited interest, with the international and the Spanish-speaking community primarily perceiving the crisis as a (diplomatic) bilateral conflict. The EU was salient only among the former while the latter also perceived the crisis as a pro- or anti- government issue. Conversely, users asserting Moroccan sovereignty and/or a boycott of Spanish products were salient, particularly in English and French.
Keywords: migratory crisis; Twitter; migration attitudes; far right; border